Harmonisasi Tiga Lingkungan Pendidikan: Studi Konsep Pendidikan Islam & Kandungan Ayat Al-Qur’an - Abu Warasy Batula; Ahmad Syakir Wildani; Bilqis Nafilah Febrianti; Silvia Siti Rachmawaty; Raka Surya Ramadhan; Muhamad Parhan; Syahidin Syahidin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research focuses on the crucial role of the Islamic educational environment in supporting an effective educational process. Qualitative methods and literature analysis were employed to delve into this topic. Although the Quran doesn't explicitly address it, Islamic history reveals attention to educational settings like mosques, homes, madrasahs, and universities. In Islam, families hold a primary role in creating an educative atmosphere for children. Preparing parents before forming a family is pivotal in Islamic education, with the concepts of a peaceful, loving, and compassionate family serving as essential foundations. Schools and madrasahs contribute to shaping Islamic character in students, despite the term "madrasah" not being explicitly mentioned in the Quran. Other Islamic educational institutions such as pesantrens and universities also contribute to teaching Islamic knowledge. The community environment also plays a role in informal education, bearing the responsibility of educating the younger generation. Harmonious coordination among families, schools, and communities is considered crucial in aligning education to achieve desired goals. The concept of ongoing improvement in educational institutions becomes vital to anticipate changes in the educational environment, involving all stakeholders in identifying and utilizing opportunities for enhancement. Sustaining harmonious coordination within the educational environment fosters an educational process that meets contemporary needs.